Electromagnetic researches in area of the observatorie Acad. Vernadsky (Antarctic Peninsula) - I. M. Logvinov; V. Tarasov; B. T. Ladanivsky (Ukrainian Antarctic Journal, 2006)
On the data of supervision of variations of a geomagnetic field of the induction arrows Сu and Cv in in the period range 36 to 10800 s with on observatories VRN and nearby islands Berthelot, Petermann are received. According to one-dimensional inversion of the data MTS in obs. VRN in a geoelectrical section of region there are no well conducting objects in bottoms crust and upper mantle. The results carried out 2D of modeling along a profile crossing the Antarctic peninsula allow to offer a technique of realization of experimental supervision, with which help it is possible to reveal of geoelectrical heterogeneity in a structure crust and upper mantle of the region.